Knowledge, Attitudes, and Practices of Medical University Students Toward Antibiotics and Antimicrobial Resistance - khriesat, wadah; Khriesat, Mohammad; Kassab , Manal (Jordan Medical Journal, 2025)
Background: Antimicrobial resistance (AMR) is a growing concern worldwide. The inappropriate use of antibiotics leads to antibiotic resistance, which reduces their efficacy. Assessing awareness is, therefore, critical in the effort to confront the spread of antibiotic resistance. Medical students are potential antimicrobial prescribers and stewards following graduation as clinicians . The education of undergraduate students is likely to influence their practices. Assessing awareness is critical in the general effort to confront the spread of antibiotic resistance. Appropriate studies regarding the knowledge, attitudes, and practices of medical students in Jordan regarding antibiotic use and antimicrobial resistance are nonexistent. The aim of this study was to assess knowledge regarding antibiotic use and resistance among medical students in Jordan in their clinical years. Methods: A cross-sectional study was performed, using a sampling frame of medical students of the 4th, 5th, and 6th academic years at the Jordan University of Science and Technology. A total of 587 students were involved. The study was conducted from November 1st, 2022 to February 1st, 2023. The survey was anonymous and self-administered. The data were collected from an online survey questionnaire and analyzed. Results: A total of 587 students responded; 42.9% were male (n=252) and 57.0% female (n=335). The response rate was 94%. 87% desired more education on antibiotic use and resistance. The majority (64.7%) of respondents had good knowledge of antibiotic use and resistance; however, 39% incorrectly answered that bacteria would cause common cold. Only 56.0% reported positive practice of antibiotic use. While 8.2% of respondents always consulted a clinician before starting an antibiotic, and 37.2% never discarded their remaining leftover medications. Knowledge was significantly associated with the academic year (p<0.0001) Conclusion: This study provided the first prevalence data on antibiotic use and knowledge of antibiotics and AMR among medical undergraduate students in Jordan. The study results indicated that current medical education has appropriately influenced the quality use of antibiotics among medical students in Jordan.